Nanogenerator-based self-powered sensors for data collection - Shao, Yicheng; Shen, Maoliang; Zhou, Yuankai; Cui, Xin; Li, Lijie; Zhang, Yan (Beilstein Journal of Nanotechnology, 2021)
Self-powered sensors can provide energy and environmental data for applications regarding the Internet of Things, big data, and artificial intelligence. Nanogenerators provide excellent material compatibility, which also leads to a rich variety of nanogenerator-based self-powered sensors. This article reviews the development of nanogenerator-based self-powered sensors for the collection of human physiological data and external environmental data. Nanogenerator-based self-powered sensors can be designed to detect physiological data as wearable and implantable devices. Nanogenerator-based self-powered sensors are a solution for collecting data and expanding data dimensions in a future intelligent society. The future key challenges and potential solutions regarding nanogenerator-based self-powered sensors are discussed.
Keywords: data collection; Internet of Things; nanogenerator; self-powered sensor; wearable device